Anansi and the Magic Stick - Kimmel, Eric A.; Stevens, Janet (New York : Holiday House, 2001)
Anansi the Spider steals Hyena's magic stick so he won't have to do the chores, but when the stick's magic won't stop, he gets more than he bargained for.
Keywords: Anansi (Legendary character); Folklore -- West Africa